RESEARCH INFO FOLK BOOKS IN THE WORK OF FRATERNAL PEOPLES (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
Folklore the beginning of the art of words, has been a constant companion of  people’s life in every era. In the second half of  the 19 th century, Nurota and  Bulungur  schools, which  were  the major centers of folk  art appeared. In the research, it  was noted  that V.Abdullayev wrofe  many such works of oral creativity among  the uzbek, Turkmen, Karakalpak and Kazakh peoples  in the  18th-19th centuries  and had appositive  impact on the  development of  written literature.It is reflected that the scientific -theoretical views on the nature of  flok  books, which are considered acommon phenomenon of  folk studies, served  as the result  of the first  researches in  the history  of uzbek literary studies.